2018
DOI: 10.1007/s00436-018-5890-y
|View full text |Cite
|
Sign up to set email alerts
|

A review of coccidiosis in South American camelids

Abstract: Camelids (llamas, alpacas, vicuñas, guanacos) are important for the economy of South America and Eimeria infections are important as cause of mortality in camelids. Of the five most prevalent species of Eimeria in South American camelids, Eimeria macusaniensis, Eimeria lamae, Eimeria alpacae, Eimeria punoensis, and Eimeria ivitaensis, E. macusaniensis is considered the most pathogenic. There is considerable confusion concerning the endogenous developmental stages of Eimeria spp. in camelids. Many papers on cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 46 publications
4
30
0
1
Order By: Relevance
“…Due to the high host specificity Eimeria spp. are not transmitted between South American camelids and other species [21, 22]. As we examined only animals older than one year we found mostly very low or low excretion densities; however, in some cases animals shed considerable amounts of oocysts, indicating that coccidiosis may occur in alpacas under unfavourable conditions on the farm or might be facilitated by a poor immune status of the animals.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Due to the high host specificity Eimeria spp. are not transmitted between South American camelids and other species [21, 22]. As we examined only animals older than one year we found mostly very low or low excretion densities; however, in some cases animals shed considerable amounts of oocysts, indicating that coccidiosis may occur in alpacas under unfavourable conditions on the farm or might be facilitated by a poor immune status of the animals.…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, coccidia (genus Eimeria ) were the most common endoparasites detected. In South American camelids, five different Eimeria species ( E. alpacae , E. lamae , E. punoensis , E. macusaniensis and rarely E. ivitaenis ) can be found [5, 21]; E. peruviana is currently not validated as a species. Especially E. macusaniensis is frequently implemented in clinical cases [2123].…”
Section: Discussionmentioning
confidence: 99%
“…For example, genome sequencing from phylogenetically distinct species such as E. gruis and E. reichenowi from migratory crane [ 18 ] may inform on phenotypes associated with disseminated visceral coccidiosis, possibly revealing new genera. Similarly, accessing genomes of atypical Eimeria species such as E. leuckarti , E. macusaniensis , E. truncata and E. stiedai , from horses, alpacas, geese and rabbits, respectively [ 58 , 59 , 60 , 61 ], may offer insights into their unique biologies.…”
Section: Comparative Genomicsmentioning
confidence: 99%
“…Authors found the five most pathogenic species to be Emeria macusaniensis , Eimeria lamae , Eimeria alpacae , Eimeria punoensis and Eimeria ivataensis . With Eimeria macusaniensis considered as the most pathogenic species for South American Camelids [26].…”
Section: South American Camelids (Lama Gunacoa Lama Glama Lama Pmentioning
confidence: 99%